In vitro assessment of pancreatic hormone secretion from isolated porcine islets - Mourad, Nizar I.; Xhema, Daela; Gianello, Pierre (Frontiers in Endocrinology, 2022)
The potential use of porcine islets for transplantation in humans has triggered interest in understanding porcine islet physiology. However, the number of studies dedicated to this topic has remained limited, as most islet physiologists prefer to use the less time-consuming rodent model or the more clinically relevant human islet. An often-overlooked aspect of pig islet physiology is its alpha cell activity and regulation of its glucagon secretion. In vitro islet perifusion is a reliable method to study the dynamics of hormone secretion in response to different stimuli. We thus used this method to quantify and study glucagon secretion from pig islets. Pancreatic islets were isolated from 20 neonatal (14 to 21-day old) and 5 adult (>2 years) pigs and cultured in appropriate media. Islet perifusion experiments were performed 8 to 10 days post-isolation for neonatal islets and 1 to 2 days post-isolation for adult islets. Insulin and glucagon were quantified in perifusion effluent fractions as well as in islet extracts by RIA. Increasing glucose concentration from 1 mM to 15 mM markedly inhibited glucagon secretion independently of animal age. Interestingly, the effect of high glucose was more drastic on glucagon secretion compared to its effect on insulin secretion. In vivo, glucose injection during IVGTT initiated a quick (2-10 minutes) 3-fold decrease of plasmatic glucagon whereas the increase of plasmatic insulin took 20 minutes to become significant. These results suggest that regulation of glucagon secretion significantly contributes to glucose homeostasis in pigs and might compensate for the mild changes in insulin secretion in response to changes in glucose concentration.